ANTIFUNGAL ACTIVITY OF SOME PLANT EXTRACTS AGAINST FUNGUS FUSARIUM OXYSPORUM - SHAREEF, BAREEN SDQI; ALI, ALI SAMI; ALI , SHREEN GHAEB; TAHER, IBRAHIM ESSA (Journal of Duhok University, 2022)
In vitro, study was conducted to evaluate the efficiency of leaves extracts for each of Nerium oleander , Eucalyptus camaldulensis and Myrtus communis at concentrations  (0, 20, 30, and 50 )% on the growth and sporulation of Fusarium oxysporum . In addition to the control, the experiment included three concentration levels for each aqueous plant extract: 20%, 30%, and 50%. When compared to the control, all plant extracts inhibited fungal growth in (Fusarium oxysporum). The greatest inhibitory effect was found to be 31.158 percent. Azadirachta indica has proven to be the most effective in reducing fungal growth